Specific Changes in Hemostasis System Parameters during Extracorporeal Membrane Oxygenation in Patients with a Novel Coronavirus Infection - Zhuravel, S. V.; Ivanov, I. V.; Talyzin, A. M.; Klychnikova, E. V.; Bulanov, A. Yu; Popugaev, K. A.; Vladimirov, V. V.; Tazina, E. V.; Petrikov, S. S. (Vestnik anesteziologii i reanimatologii, 2022)
Extracorporeal membrane oxygenation (ECMO) is a method that makes it possible to compensate for critical changes caused by acute respiratory failure, with the ineffectiveness of treatment with rigid modes of artificial lung ventilation (ventilator) in patients with acute respiratory distress syndrome in intensive care units. The search for the optimal state of the hemostasis system is one of the main tasks in the treatment of critical patients in ECMO conditions. The objective: to study changes in hemostatic parameters in patients with COVID-19 undergoing ECMO and determine the need for their correction. Subjects and Methods. According to the inclusion and exclusion criteria, 100 patients were included in the study: 72 men and 28 women aged 26 to 75 years old, the median age made 55 years [47; 60]. VV-ECMO was performed in all observations. In 100% of cases, the cause of respiratory failure which required VV-ECMO was COVID-19-associated pneumonia. Results. 49 episodes of hemorrhagic complications and 76 episodes of thrombotic complications were recorded from the 1st to the 7th day from the moment of ECMO initiation. We found that the chance of developing thrombosis decreased by an average of 0.3% with an increase in the activity of antithrombin-3 by 1%. A statistically significant association of thrombosis risk was also found for prothrombin and prothrombin time. Conclusion. During the first 7 days of ECMO, patients with COVID-19 demonstrate the increase in APTT, prothrombin time and a decrease in the number of platelets, prothrombin activity, and fibrinogen concentration. The risk of thrombosis in this group of patients significantly decreases with the increasing activity of antithrombin-3 and prothrombin and increases with rising need of the higher dose of unfractionated heparin. The tactics of restrictive anticoagulant therapy when using unfractionated heparin can be taken into account as a way to reduce the risk of thrombosis and requires further research.